Identifying Priorities and Strategies for Improving Colorectal Cancer Screening in Tribal Clinics - Jessica Blanchard; Dorothy Rhoades; Zsolt Nagykaldi; Janis Campbell; Tamela Cannady; Michelle Hopkins; Michelle Gibson; Hazel Lonewolf; Mark Doescher (Cancer Control, 2022)
Background Colorectal cancer (CRC) is the 3 rd most frequently diagnosed cancer and the 2 nd leading cause of cancer death in the United States (US), and incidence and mortality rates in Oklahoma are higher for many American Indian (AI) populations than other populations. The AI CRC Screening Consortium addresses major regional CRC screening disparities among AIs with shared objectives to increase CRC screening delivery and uptake in AIs aged 50 to 75 years at average risk for CRC and to assess the effectiveness of implementations of the interventions. This manuscript reports environmental scan findings related to current practices and multi-stakeholder experiences with CRC screening in two Oklahoma Indian health care systems. Method We conducted a mixed methods environmental scan across five clinical sites and with multiple stakeholders to determine the scope and scale of colorectal cancer screening in two separate AI health care delivery systems in Oklahoma. Data collection consisted of a mixture of individual interviews and group discussions at an urban site, and four clinical care sites within a tribal health system. Results Sixty-two individuals completed interviews. Data from these interviews will inform the development of evidence-based intervention strategies to increase provider delivery, community access to, and community priority for CRC screening in diverse AI health care delivery systems. Conversations with patients, providers, and clinical leadership point to individual and system-level opportunities for improvement at each site, shaped in part by differences in the delivery of services, structure of the health care system, and capacity to implement new intervention strategies. The thematic areas most central to the process of evidenced-based intervention development included: current practices, needs and recommendations, and CRC site priorities. Conclusion Environmental scan data indicated clear opportunities for individual and system-level interventions to enhance CRC screening and was critical for understanding readiness for EBI implementation at each site.